Exploring nursing and medical perceptions of sepsis management in a New Zealand emergency department: A qualitative study. (9th December 2021) - Rogan, Alice; Lockett, Jessica; Peckler, Brad; Robinson, Brian; Raymond, Nigel
Abstract: Objective: Early sepsis recognition and treatment are essential in order to reduce the burden of disease. Initial assessment of patients with infection is often undertaken by ED nurses and resident doctors. This descriptive qualitative study aimed to explore their perceptions and perspectives regarding the factors that impede the identification and management of patients with sepsis. Methods: This was a qualitative study conducted between 30 January 2020 and 27 February 2020. Semi‐structured focus group interviews were performed to collect data. All participants provided written informed consent and completed a basic demographic and work experience form. Two study investigators facilitated the interviews. Interviews were audio‐recorded and later transcribed. Thematic analysis was performed with the aid of NVivo 12 software. Results: Six focus group interviews were conducted involving 40 ED nurses and doctors. Interview length ranged from 27 to 38 min (mean 33.5 min). Three major themes were identified: (i) clinical management; (ii) challenges and delays; and (iii) communication. Each of these themes was broken down into subthemes, which are presented in more detail. Conclusion: ED nurses and doctors have identified important factors that limit and enhance their capacity to recognise and respond to patients with sepsis. Complex interactions exist between clinical and organisational structures that can affect the care of patients and the ability of clinicians to provide optimal care. The three major themes and specific subthemes provide a useful framework and stimulus for service improvements and research that could help foster future sepsis management improvement strategies. Abstract : ED nurses and doctors have identified important factors that limit and enhance their capacity to recognise and respond to patients with sepsis. Complex interactions exist between clinical and organisational structures that can affect the care of patients and the ability of clinicians to provide optimal care. The three major themes and specific subthemes provide a useful framework and stimulus for service improvements and research that could help foster future sepsis management improvement strategies.